Coating Strategies Using Layer‐by‐layer Deposition for Cell Encapsulation. Issue 12 (23rd May 2016) - Oliveira, Mariana B.; Hatami, Javad; Mano, João F.
Abstract: The layer‐by‐layer (LbL) deposition technique is widely used to develop multilayered films based on the directed assembly of complementary materials. In the last decade, thin multilayers prepared by LbL deposition have been applied in biological fields, namely, for cellular encapsulation, due to their versatile processing and tunable properties. Their use was suggested as an alternative approach to overcome the drawbacks of bulk hydrogels, for endocrine cells transplantation or tissue engineering approaches, as effective cytoprotective agents, or as a way to control cell division. Nanostructured multilayered materials are currently used in the nanomodification of the surfaces of single cells and cell aggregates, and are also suitable as coatings for cell‐laden hydrogels or other biomaterials, which may later be transformed to highly permeable hollow capsules. In this Focus Review, we discuss the applications of LbL cell encapsulation in distinct fields, including cell therapy, regenerative medicine, and biotechnological applications. Insights regarding practical aspects required to employ LbL for cell encapsulation are also provided. Abstract : Dressed up to be functional : In this Focus Review the use of nanostructured multilayer coatings for cell encapsulation is discussed. Furthermore, their role in direct cellular surface modification of single cells and cellular aggregates, as well as in the coating of biomaterials for functionalization or design of hollow capsules is discussed. Insights regarding the optimization of such systems are also provided.